Functional and Amylographic Properties of Physically-Modified Sweet Potato Starch - Marta, Herlina; Tensiska, Tensiska (KnE Life Sciences, 2017)
In general, native sweet potato starch has inferior characteristics such as it swells easily, does not gel firmly and low paste clarity. The characteristics of native sweet potato starch cause limitation in its utilization. This research aimed to study the effect of physically modified starch on the functional and amylographic properties of native sweet potato starch. The study used a descriptive method with 4 treatments and 2 replications: a) a native sweet potato starch, b) sweet potato modified starch by heat moisture treatment, c) sweet potato starch modified by annealing and d) sweet potato starch modified by pre-gelatinization. The results showed that all three treatments modified starches largely alter the functional and amylographic properties of native sweet potato starch. Heat moisture treated and annealed sweet potato had starches with decreased swelling volume, solubility, peak viscosity, and breakdown viscosity, increased pasting temperature and setback viscosity than its native starch. Pre-gelatinized sweet potato starch has lower bulk density, peak viscosity, breakdown viscosity, setback viscosity and increased swelling volume, solubility and water absorption capacity than its native starch. Key word: functional properties; amylographic properties; sweet potato starch; physically modified